WHEAT VARIETIES PRODUCTION UNDER DIFFERENT IRRIGATION LEVELS UTILIZING AQUACROP MODEL IN SEMIARID CONDITION OF DUHOK –IRAQI KURDISTAN - & et al., Dilsher (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was conducted at the research farm of the College of Agriculture, University of Duhok, Iraq Kurdistan Region season of 2015-2016. Irrigation treatments include (Rainfed, 50% and 100% of field capacity). with three broad wheat varieties (IPA-95, Abu-Graib and Sham-4) cultivated by application the (AquaCrop) model. Wheat varieties of IPA-95 and Abu-Graib-3 consistently resulted in higher yields than Sham-4 variety, the highest grain yield of 3.872 t. ha-1 was recorded by IPA-95 variety. Highest grain yield of 3.78 t.ha-1 was obtained from Total Field Capacity. The biomass varied from 12.162, 12.214 and 13.056, 11.591 and 11.211 to 11.866 t.ha-1 for measured and simulated values. Also the results indicated that the highest crop water productivity of grain yield was obtained by Abu-Graib-3 in both measured and simulated water productivity kg.m-3 which were (5.404 and5.767 kg.m3).